The Multifactorial Role of Peripheral Nervous System in Bone Growth - Gkiatas, Ioannis; Papadopoulos, Dimitrios; Pakos, Emilios E.; Kostas-Agnantis, Ioannis; Gelalis, Ioannis; Vekris, Marios; Korompilias, Anastasios (Frontiers in Physics, 2017)
Bone alters its metabolic and anabolic activities in response to the variety of systemic and local factors such as hormones and growth factors. Classical observations describing abundance of the nerve fibers in bone also predict a paradigm that the nervous system influences bone metabolism and anabolism. Since 1916 several investigators tried to analyze the effect of peripheral nervous system in bone growth and most of them advocated for the positive effect of innervation in the bones of growing organisms. Moreover, neuronal tissue controls bone formation and remodeling. The purpose of this mini-review is to present the most recent data concerning the influence of innervation on bone growth, the current understanding of the skeletal innervation and their proposed physiological effects on bone metabolism as well as the implication of denervation in human skeletal biology in the developing organism since the peripheral neural trauma as well as peripheral neuropathies are common and they have impact on the growing skeleton.